The Norwegian Cash-for-Care Reform. Changing behaviour and stable attitudes - Gulbrandsen, Lars (Nordisk barnehageforskning, 2009)
In 1998 Norway introduced a cash-for-care scheme. Parent with children aged one or two were offered a cash-for-care benefit if they did not make use of public funded day care centres. The reform was supported by political parties of the centre and right and strongly opposed by parties on the left. Since 1999 ever fewer parents have made use of the opportunity to claim the benefit and have instead sent their children to a day care centre. Attitudes towards the cash-for-care reform, however, have remained very stable up to now. The principle of freedom of choice appears to be strongly rooted among Norwegians. The political agreement on maximum prices made this freedom a reality even for parents who wanted to make use of child care centres.